Identification of in-service training needs among secondary school clerks in Kuching division, Sarawak - John, Mary (2002)
The purpose of this study is to identify the in-service training needs of secondary school clerks in Kuching Division, Sarawak. Related to those needs, preferences of the clerks pertaining to duration, location and trainers for the training programme will also be determined.